BUDAYA HUKUM DALAM PENYALURAN KREDIT BISNIS PERBANKAN DI INDONESIA - Widya Permata Sari; Ilham Kurniawan; Elsi Kartika Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study examines the crisis and transformation of legal culture within banking credit practices in Indonesia through a juridical and sociological analysis of the Supreme Court Decision No. 1102 PK/Pid.Sus/2024. Drawing on Lawrence M. Friedman’s theory of legal culture, Satjipto Rahardjo’s progressive law, and Mochtar Kusumaatmadja’s concept of law as a tool of social engineering, the study reveals a paradigm shift in the banking sector from moral-ethical legal orientation and substantive justice toward formal legality and economic pragmatism. The improper issuance of a Rp39.5 billion credit facility—later classified as a mere “business risk”—illustrates weakened compliance culture, diminished integrity, and the erosion of fiduciary responsibility within banking institutions. Findings highlight a widening gap between law in the books and law in action, inadequate internal and external supervision, and a cultural lag between rapid socio-economic changes and the development of legal values. Consequently, the law loses its moral, preventive, and corrective functions in guiding corporate behavior. This research emphasizes the urgency of reconstructing legal culture in banking through strengthening substantive justice, integrity, Good Corporate Governance, and corporate social responsibility to restore ethical, just, and sustainable legal governance in Indonesia’s banking system.Keywords: legal culture, banking law, prudential principle, law enforcement, non-performing loans